2013
DOI: 10.1074/jbc.m113.477067
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Bacterial Peroxidase with Novel Halogenating Activity and an Autocatalytically Linked Heme Prosthetic Group

Abstract: Background: First analysis was made of bacterial ancestor of peroxidases from mammalian innate immune system. Results: Highly stable heme enzyme possesses high bromination activity and covalently bound prosthetic group. Conclusion: Post-translational autocatalytic (peroxide-driven) heme modification is found in prokaryotic and eukaryotic halogenating peroxidases. Significance: Peroxidase-mediated production of antimicrobial hypohalous acids was developed early in evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…Human peroxidases, like lactoperoxidase, eosinophil peroxidase and thyroid peroxidase autocatalytically form covalent haeme to protein ester linkages [50], whereas in myeloperoxidase an additional sulfonium linkage between a haeme vinyl group and a methionine is found [51]. Recently, it was shown that also some bacterial peroxidases establish covalent haeme to protein ester bonds [52,53]. However, in most haeme proteins the Fe-proximal His represents the only covalent bond between the haeme chromophore and the protein, and stable incorporation of the prosthetic group occurs via several non-covalent interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Human peroxidases, like lactoperoxidase, eosinophil peroxidase and thyroid peroxidase autocatalytically form covalent haeme to protein ester linkages [50], whereas in myeloperoxidase an additional sulfonium linkage between a haeme vinyl group and a methionine is found [51]. Recently, it was shown that also some bacterial peroxidases establish covalent haeme to protein ester bonds [52,53]. However, in most haeme proteins the Fe-proximal His represents the only covalent bond between the haeme chromophore and the protein, and stable incorporation of the prosthetic group occurs via several non-covalent interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For ECD, Chirascan from Applied Photophysics (Leatherhead, UK) was used, and changes of the ellipticity at 208 nm as well as at 412 nm in 20 mM phosphate buffer, pH 7.4, with increasing temperature were recorded and evaluated (29). The instrument was flushed with nitrogen at a flow rate of 5 liters min Ϫ1 and was equipped with a Peltier element for temperature control.…”
Section: Mass Spectrometric Analysis Of Cysteines and Cystines-mentioning
confidence: 99%
“…These proteins have sequence similarity to animal heme peroxidases of the peroxidase-cyclooxygenase superfamily of peroxidases (18). This class of enzymes includes myeloperoxidases (MPO) and lactoperoxidases (LPO), which use hydrogen peroxide as the oxidant and, as their names suggest, contain a heme cofactor.…”
mentioning
confidence: 99%
“…This class of enzymes includes myeloperoxidases (MPO) and lactoperoxidases (LPO), which use hydrogen peroxide as the oxidant and, as their names suggest, contain a heme cofactor. These animal heme peroxidases generally consist of the peroxidase domain and another nonenzymatic domain (18,19). The Mn-oxidizing proteins (MopAs) of this type have been identified in Erythrobacter sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation